Injuries in breaking: An overview and synthesis of case reports and letters to the editor - Brborovic, H.; Lindner, S. M.; Brborovic, O.; Weinrich, L. (Journal of Dance Medicine & Science, 2026)
Introduction: Breaking, also known as breakdancing, has evolved from street culture to a structured sport, debuting in the 2024 Olympics. Despite its popularity, limited data exists on injury prevalence, types, and risk factors associated with acute and overuse injuries sustained from breaking. While existing studies offer insights into common injury patterns, they provide limited analysis of the specific mechanisms behind these injuries. This overview aims to classify acute and overuse injuries in breaking, reviewing 50 years of literature to identify risk factors and high-risk movements.